Modeling and Microfabrication of a CMOS Resonator for Magnetic Field Measurement - Dennis , John Ojur (2012)
This paper presents the modeling and microfabrication of a CMOS resonant magnetic field sensor capable of measuring magnetic field in the range of nanotesla. This sensor is based on differential electrostatic along with Lorentz force actuation and piezoresistive sensing. Cadence virtuoso layout is used to design the resonant magnetic sensor for fabrication. Using microfabrication facilities of MIMOS Bhd all CMOS layers i.e. three metal and two poly layers are used to fabricate the magnetic sensor to enhance the sensitivity. At sensor output, without any amplification its sensitivity is 1.4807 mV/mT at 0.001 damping ratio with quality factor 500 and resonant frequency 9.35 kHz.